DISTINGUISHING MODES OF LEUKOCYTE CELL DEATH USING FLOW CYTOMETRY IN CHRONIC RHINOSINUSITIS WITHOUT NASAL POLYPS - Onishchenko, Anatolii I.; Tkachenko, Anton S.; Kalashnyk, Julii M.; Zubov, Pavel M.; Gorbach, Tatyana V.; Babijchuk, Lyubov A.; Nakonechna, Oksana A. (Medicinski časopis, 2019)
Objective. The objective of our research is to study the rate and modes of cell death among nucleated peripheral blood cells using annexin V and 7-AAD flow cytometry kits in patients with CRSsNP. Methods. Flow cytometry was used to detect nucleated blood cells apoptosis stages in twelve patients with CRSsNP. Annexin V FITC, CD45 PE and 7-AAD markers (7-aminoactinomycin D) were used for the assessment of apoptosis stages. The current method allows identifying four different states of cells: 1 - viable cells (AnnexinV-7AAD- - cells); 2 – early apoptotic cells (AnnexinV+7AAD- - cells); 3 - late apoptotic/necrotic cells (AnnexinV+7AAD+ - cells); 4 - dead necrotic cells (AnnexinV-7AAD+ - cells). To assess the rate of oxidative stress in CRSsNP, 8-isoprostane levels in blood serum were determined using ELISA. Results. We found that CRSsNP was accompanied by the development of oxidative stress and the increased rate of cell death among nucleated peripheral blood cells with the prevalence of early apoptotic cells. Early apoptotic cells were effectively removed from the bloodstream by phagocytes, which can be judged from the less noticeable increase in the percentage of late apoptotic/necrotic leukocytes compared to the control group. Conclusion. We can make a conclusion that the changes in the percentage of dead cells and modes of cell death of nucleated peripheral blood cells in patients with CRSsNP may be due to the activation of mechanisms aiming at preventing the overintensification of the inflammatory response and the damage to host tissues. Keywords: chronic rhinosinusitis, cell death, apoptosis, necrosis, flow cytometry